CNTN4 modulates neural elongation through interplay with APP - Bamford, Rosemary A.; Zuko, Amila; Eve, Madeline; Sprengers, Jan J.; Post, Harm; Taggenbrock, Renske L. R. E.; Fäßler, Dominique; Mehr, Annika; Jones, Owen J. R.; Kudzinskas, Aurimas; Gandawijaya, Josan; Müller, Ulrike C.; et al. (Open biology, 2024)
The neuronal cell adhesion molecule contactin-4 (CNTN4) is genetically associated with autism spectrum disorder (ASD) and other psychiatric disorders. Cntn4-deficient mouse models have previously shown that CNTN4 plays important roles in axon guidance and synaptic plasticity in the hippocampus. However, the pathogenesis and functional role of CNTN4 in the cortex has not yet been investigated. Our study found a reduction in cortical thickness in the motor cortex of Cntn4 −/− mice, but cortical cell migration and differentiation were unaffected. Significant morphological changes were observed in neurons in the M1 region of the motor cortex, indicating that CNTN4 is also involved in the morphology and spine density of neurons in the motor cortex. Furthermore, mass spectrometry analysis identified an interaction partner for CNTN4, confirming an interaction between CNTN4 and amyloid-precursor protein (APP). Knockout human cells for CNTN4 and/or APP revealed a relationship between CNTN4 and APP. This study demonstrates that CNTN4 contributes to cortical development and that binding and interplay with APP controls neural elongation. This is an important finding for understanding the physiological function of APP, a key protein for Alzheimer’s disease. The binding between CNTN4 and APP, which is involved in neurodevelopment, is essential for healthy nerve outgrowth.
Online veröffentlicht: 15.05.2024
Gesehen am 25.03.2025